PERFORMANCE OF FULL SCALE TEST EMBANKMENT WITH REINFORCED LIGHTWEIGHT GEOMATERIALS ON SOFT GROUND - T. Tanchaisawat; P. Voottipruex; D. T. Bergado; S. Hayashi (International Association of Lowland Technology, 2008)
Embankment construction using reinforced lightweight geomaterials over soft ground will alleviate problems of instability and large settlements. Backfills of retaining structures can also be constructed using lightweight materials resulting in lower vertical loads and, consequently, reduced settlements. The aim of this study is to investigate the behavior of lightweight geomaterials consisting of tire chip-sand mixture reinforced with geogrids for use as embankment construction on soft ground. The experimental results indicated that the mixing ratio of 30:70 % was the most suitable fill material. The full scale field test embankment was constructed at the campus of Asian Institute of Technology (AIT) in Bangkok, Thailand. The geogrid reinforced embankment system was extensively instrumented in the subsoil and within the embankment itself in order to observe its behavior during construction and post construction phases, and thereby evaluate its performance. The unit weight of rubber tire chip-sand mixtures is about 75% lighter than conventional sand. The total settlement at ground surface is 67.5% less when compared to the conventional backfill without foundation treatments. The maximum lateral wall movement observed at 13 months after construction at top of wall is 45% smaller when compared to conventional sand backfill on untreated ground. Finally, the geogrid reinforcements correspond well with the bilinear type of maximum tension line.